Penerapan Metode Double Exponential Smoothing untuk Memprediksi Penggunaan HIPPAM (Studi Kasus; Himpunan Pemakaian Air Masda) - Octaviana Sari, Mila; Miftahus Sholihin; Agus Setia Budi (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
Clean water is an essential resource, yet its distribution often faces challenges due to population growth, seasonal changes, and consumption patterns. The Public Water Users Association (HIPPAM) in Dengok Hamlet, Kandangsemangkon Village, Lamongan Regency, plays a vital role in meeting the community’s daily water needs. This study applies the Double Exponential Smoothing (DES) method to forecast HIPPAM water demand. Consumption data from 2020 to 2024 were used, with smoothing parameters alpha (α) and beta (β) set between 0 and 1. The forecasting performance was evaluated using MAPE (Mean Absolute Percentage Error), MAD (Mean Absolute Deviation), and MSE (Mean Squared Error). Results show that the DES method achieved high accuracy, with MAPE values below 1%. Furthermore, the forecasting system was implemented as a web-based application, enabling HIPPAM managers to monitor and plan water distribution more effectively.